JAPAN'S FINANCIAL AND HUMANITARIAN ASSISTANCE TO UKRAINE DURING THE PERIOD OF FULL-SCALE RUSSIAN AGGRESSION (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Russian aggression has given a new impetus to the development of Ukrainian-Japanese relations. Japanese diplomacy is extremely active in supporting Ukraine and fighting Russian aggression. Japan is not only a technological superpower, but also an active member of the G-7, and thus a significant player in the global world whose opinion is not ignored in the political environment. Russia's war against Ukraine has affected both Japan's domestic policy and finally adjusted the vector of its foreign actions in the international arena against the new «axis of evil».The Ukraine-Russia war has moved from the format of regional confrontation to the confrontation between democracy and authoritarianism. This requires fundamental changes in Ukraine's foreign policy towards a number of Southeast Asian countries, namely their attitude to the largest military conflict in Europe in the first quarter of the twenty-first century.This research examines Ukrainian-Japanese political and economic relations over the past nine years. The author identifies the priority directions of Japan's foreign policy towards Ukraine at the present stage, the mechanisms of their implementation and the place of Ukrainian-Japanese relations in the system of values of each state. The main spheres of Japan's economic diplomacy are analyzed on the example of Ukraine before the active phase of armed aggression and after the outbreak of active hostilities. Specific examples of non-military financial and humanitarian assistance provided by the Japanese government to Ukraine during the war are considered.Particular attention is paid to the promising areas of cooperation between the two countries on the restoration of Ukraine's economy after the liberation of the territory of Ukraine. It will include the development and implementation of modern energy-saving technologies in the energy, industry, and municipal sectors, attracting Japanese investments in the reconstruction and development of Ukraine's transport and energy infrastructure, and restoring the agricultural sector. In the international arena, Japan has long been a staunch supporter of Ukraine's «sovereignty and territorial integrity». Ukraine emphasizes expanding the number of members of the UN Council to include Japan as a permanent member of the UN Council and opposing the «veto power» of Russia and China in resolving key political issues.
Keywords: Japan-Ukraine relations, financial and humanitarian aid, Russian-Ukrainian war, post-war economic recovery, investments.